Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/cells11030586
|View full text |Cite
|
Sign up to set email alerts
|

Arabinogalactan Proteins in the Digestive Glands of Dionaea muscipula J.Ellis Traps

Abstract: The arabinogalactan proteins (AGP) play important roles in plant growth and developmental processes. However, to the best of our knowledge, there is no information on the spatial distribution of AGP in the plant organs and tissues of carnivorous plants during their carnivorous cycle. The Dionaea muscipula trap forms an “external stomach” and is equipped with an effective digestive-absorbing system. Because its digestive glands are composed of specialized cells, the hypothesis that their cell walls are also ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 53 publications
3
22
0
Order By: Relevance
“…We showed that the cell wall ingrowths in the transfer cells of A. vesiculosa glands were rich in AGPs. The wall ingrowths were similar in their AGP composition (JIM8, JIM13, JIM14) to the wall ingrowths in the transfer cells of D. muscipula digestive glands [ 18 ]. It was shown that the epitope recognized by JIM14 was a useful marker of the digestive glands of D. muscipula .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We showed that the cell wall ingrowths in the transfer cells of A. vesiculosa glands were rich in AGPs. The wall ingrowths were similar in their AGP composition (JIM8, JIM13, JIM14) to the wall ingrowths in the transfer cells of D. muscipula digestive glands [ 18 ]. It was shown that the epitope recognized by JIM14 was a useful marker of the digestive glands of D. muscipula .…”
Section: Discussionmentioning
confidence: 99%
“…In both D. muscipula and A. vesiculosa , the cell wall ingrowths in the gland cells were rich in AGPs in mature traps. It is known that AGPs play various roles in plants: developmental processes, calcium capacitor, signaling, response to biotic and abiotic stress, and sexual reproduction [ 18 , 63 , 64 , 65 , 66 , 67 , 68 ]. In Dionaea muscipula , we found differences in the occurrence of AGPs (labeled with JIM8 and JIM13) in the walls of gland secretory cells between unfed and fed traps.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations